Brittle fracture to recoverable plasticity: polytypism-dependent nanomechanics in todorokite-like nanobelts. Issue 1 (21st September 2018) - Amin Shikder, Md Ruhul; Maksud, Mahjabin; Vasudevamurthy, Gokul; Byles, Bryan W.; Cullen, David A.; More, Karren L.; Pomerantseva, Ekaterina; Subramanian, Arunkumar
Abstract : This paper shows polytypism dependent nanomechanics in todorokite-like nanobelts and reveals a plastic recovery regime in nanobelts with larger-width tunnel grains. Abstract : Atomic force microscopy (AFM) based nanomechanics experiments involving polytypic todorokite-like manganese dioxide nanobelts reveal varied nanomechanical performance regimes such as brittle fracture, near-brittle fracture, and plastic recovery within the same material system. These nanobelts are synthesized through a layer-to-tunnel material transformation pathway and contain one-dimensional tunnels, which run along their longitudinal axis and are enveloped by m × 3 MnO6 octahedral units along their walls. Depending on the extent of material transformation towards a tunneled microstructure, the nanobelts exhibit stacking disorders or polytypism where the value for m ranges from 3 to up to ∼20 within different cross-sectional regions of the same nanobelt. The observation of multiple nanomechanical performance regimes within a single material system is attributed to a combination of two factors: (a) the extent of stacking disorder or polytypism within the nanobelts, and (b) the loading (or strain) rate of the AFM nanomechanics experiment. Controllable engineering of recoverable plasticity is a particularly beneficial attribute for advancing the mechanical stability of these ceramic materials, which hold promise for insertion in multiple next-generation technological applications that range from electrical energy storage solutions to catalysis.